Factors Associated With Pathogenicity of Anti-Glomerular Basal Membrane Antibodies: A Case Report. Issue 19 (May 2016) - Ossman, Rime; Buob, David; Hellmark, Thomas; Brocheriou, Isabelle; Peltier, Julie; Tamouza, Ryad; Dahan, Karine; Hertig, Alexandre; Rondeau, Eric; Galichon, Pierre
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Antiglomerular basement membrane (GBM) disease is known as a super-acute proliferative glomerulonephritis caused by auto-antibodies targeting the NC1 domain of the α3 chain of type IV collagen. Here, we describe a case of atypical anti-GBM disease presenting as a dialysis-dependent acute renal failure with unusual mild glomerular involvement. We found that immunoglobulin G (IgG) deposits were restricted to the uncommon IgG2 and IgG4 subclasses, and that blood was positive for anti-GBM antibodies by immunofluorescence, but not by Enzyme Linked Immunosorbent Assay (ELISA). The patient was treated with plasma exchanges, corticosteroids, and cyclosphosphamide. He eventually regained a normal renal function. This case demonstrates that biopsy-proven anti-GBM disease can have reduced pathogenicity. Referring to previous studies of anti-GBM detection in the blood from healthy or minimally ill individuals, we discuss the antigenic specificities, the IgG subclasses, and the involvement of complement in this observation. We suggest that anti-GBM disease is a heterogeneous entity and that the study of IgG subclasses by immunofluorescence may help to distinguish categories with different severities.